Responsive hybrid inorganic-organic system derived from lanthanide luminescence. (May 2016) - Zhou, Zhan; Zheng, Yuhui; Jiang, Lasheng; Yang, Jinglian; Wang, Qianming
Graphical abstract: Highlights: A novel covalent hybrid material was used to detect hemoglobin. All the recognition experiments were performed in buffer solution. Porous nano-structures was extensively studied for the recognition. Abstract: Terbium ions were incorporated into new organic-inorganic matrices to achieve intense green emissions. Hemoglobin (HB) interactions lead to dramatic changes in the luminescence emission intensities. Infrared spectra, morphological studies and photoluminescence give information for the speciation and process of hemoglobin additions. The porous material has a large specific surface area of 351 cm 2 /g and the detection limit for HB (0.7 μM) was much lower than its physical doped material (8 μM). This promising hybrid material will lead to the design of versatile optical probes that are efficiently responding to the external targets.